(untitled) (Sains Humanika, 2017)
In this study, presenteeism and altruism factors were tested. Presenteeism in this study refer to the positive attitude to implement tasks by nurses. While altruism in this study refer to intrinsic motivation to help others without expecting any return. This study integrates belonging theory and social exchange theory.Â A survey were conducted on 386 nurses from Malaysiaâ€™s government hospitals. Structural Equation Modeling was carried out to examine the proposed factors of the research model. Finding proved presenteeism and altruism affected nurseâ€™s knowledge sharing behavior.